The development of a GC-FID method for indirect quantification of chloroacetyl chloride, a potential genotoxic impurity, in chlordiazepoxide hydrochloride drug substance - Srinivas Birudukota, Bhaskar Mangalapu, Ramesha Andagar Ramakrishna, Swagata Halder, Venkata Narayana Palakollu (Journal of Applied Pharmaceutical Science, 2024)
This study presents an innovative gas chromatographic-flame ionization detection (GC-FID) method, developed and validated in accordance with The International Council for Harmonisation (ICH) guidelines, for the quantitative analysis of chloroacetyl chloride, a potentially genotoxic impurity, in chlordiazepoxide hydrochloride active pharmaceutical ingredient. Due to the reactive and genotoxic nature of chloroacetyl chloride, precise quantification is imperative in the active pharmaceutical ingredient. The proposed method involves the conversion of chloroacetyl chloride into methyl 2-chloroacetate (MCA), enabling indirect quantification via a GC-FID approach employing a DB wax column. The validated GC-FID method displays exceptional features, such as remarkable linearity, ranging from 0.38 to 1.8 ppm with a correlation coefficient of 0.9998, as well as low detection and quantification limits of 0.19 and 0.38 ppm, and the method is specific without interference. The precision of the method expressed as the % RSD was 0.53%. The sample recovery ranging from 97.3% to 101.5%, confirms the method’s accuracy. Furthermore, three different batches of chlordiazepoxide hydrochloride underwent evaluation using this method. In conclusion, this method offers a highly sensitive approach for the precise quantification of chloroacetyl chloride in chlordiazepoxide hydrochloride drug substance, thereby ensuring compliance with the stringent safety standards of the pharmaceutical industry.
Keywords: Potential genotoxic impurity, chloroacetyl chloride, chlordiazepoxide hydrochloride, method development and method validation, GC-FID